1992
DOI: 10.1002/jmor.1052110205
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and glycoconjugate histochemistry of the palpebral glands of the adult newt, Notophthalmus viridescens

Abstract: The eyelids of the newt were studied in 10 microns serial paraffin and 1-2 microns plastic sections using standard histological stains and special stains for glycoconjugates. The eyelids contain four different glands. Simple acinar serous and simple acinar mucous glands occur in the skin; unicellular mucous glands occur in the conjunctiva; and convoluted tubular seromucous glands are present in connective tissue beneath the conjunctiva. The first two are identical to cutaneous glands found elsewhere on the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…During the secretory cycle, small granules were subsequently formed. Similar results have been reported in two urodele species by Navas et al (1982) and Reyer et al (1992). In these species, secretory epithelium of serous glands consists of individual large-sized cells with acidophilic cytoplasm and small secretory granules produced at the beginning of the secretory cycle.…”
Section: Discussionsupporting
confidence: 89%
“…During the secretory cycle, small granules were subsequently formed. Similar results have been reported in two urodele species by Navas et al (1982) and Reyer et al (1992). In these species, secretory epithelium of serous glands consists of individual large-sized cells with acidophilic cytoplasm and small secretory granules produced at the beginning of the secretory cycle.…”
Section: Discussionsupporting
confidence: 89%
“…The cell membrane disappears from the core of the gland during the final stage of maturation. It results in a syncytial gland (Navas, Bueno, Hidalgo, Aijon, & Lopez-Campos, 1982;Reyer, Liou, & Pinkstaff, 1992. Syncytial granular glands have already been described in the caecilian amphibians (Lawson, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that small, immature, organelle-rich and vesicle-poor cells are located in the apical gland pole and that large, mature, organelle-poor and vesicle-rich cells are found in the basal gland pole, strengths the hypothesis that secretory cells proliferate from apical to basal within the MGs. Earlier authors reported that a myoepithelium in MGs is absent or poorly developed and discontinuous (Dawson, 1920;Quay, 1972;Reyer et al, 1992). Some authors (Helf and Stark, 1941;Quay, 1972;Hoffman and Dent, 1978) also observed glandular secretion in the MG-lumen and argued that MGs secrete in an apocrine way, continuously secreting mucus to the exterior.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors agree that amphibian skin contains two main glandular types: first, the lumenbearing mucous glands with cells containing flocculent to granular material, second the granular (''serous'') glands which often form syncytia and are built up by cells containing granular material (Reyer et al, 1992;e.g., Duellman and Trueb, 1994;Toledo and Jared, 1995;Fontana et al, 2006). MGs are mainly responsible for producing mucopolysaccharides and mucoproteoglycans.…”
Section: Discussionmentioning
confidence: 99%